STMO-10 SURGICAL RESECTION FOR PRIMARY MOTOR CORTEX GLIOMA, TWO CASE REPORTS. (16th December 2019) - Kijima, Noriyuki; Kinoshita, Manabu; Hirayama, Ryuichi; Umehara, Tohru; Yokota, Chisato; Kagawa, Naoki; Kishima, Haruhiko
Abstract: Primary motor cortex glioma is usually considered unresectable because of its high risk for motor deficit. However recent reports suggest that surgical resections for primary motor cortex brain tumor is feasible for selected patients. In this case report, we report two cases we can successfully resected primary motor cortex glioma by awake surgery without neurological worsening. Case1 was 32 year-old woman with right primary motor cortex oligodendroglioma. We could only perform biopsy at initial surgery, however the patient got worsening of left hemiparesis which were gradually improved by rehabilitation. The patient underwent 50 Gy of radiation therapy and 6 courses of PCV chemotherapy. 60 months after the initial surgery, the tumor recurred and the she underwent 12 courses of temozolomide chemotherapy, but tumor continued to grow. She underwent second surgery 13 years after the initial biopsy. We resected primary motor cortex tumor by awake surgery without neurological complication. Case2 was 31 year-old woman with left primary motor cortex oligodendroglioma. We could only perform biopsy at initial surgery, however the patient got mild right hemiparesis which were improved by rehabilitation. The patient underwent 4 courses of PAV chemotherapy and 54 Gy of Intensity Modulated Radiation Therapy (IMRT). 21 months after IMRT, the tumor recurred and the she underwent second surgery. We resected primary motor cortex tumor by awake motor mapping without severe neurological complication. In conclusion, surgical resections for primary motor cortex glioma is feasible in selected patients without severe neurological complication. Neural plasticity is the reason for this, but careful intraoperative awake mapping is necessary to achieve maximum resections.